The greenhouse gas balance of the oil palm industry in colombia: a preliminary analysis. ii. greenhouse gas emissions and the carbon budget (2012)
In the preceding paper we examined carbon sequestration in oil palm plantations and in mill products and by-products as part of a study of the greenhouse gas balance of palm oil production in Colombia, showing how this has changed over time. Here, we look at the opposing processes of greenhouse gas (GHG) emission and calculate the resulting net carbon budget for the industry. The main emission sources, in decreasing order of magnitude, assessed using ‘default’ or ‘most probable’ options, were found to be land use change (40.9% of total), mill methane production (21.4%), direct use of fossil fuel (18.5%), indirect use of fossil fuel (11.9%) and nitrous oxide production (7.3%). The total (gross) emissions, expressed in carbon equivalents (Ceq.), were less than the amount of sequestered carbon, resulting in a positive net Ceq. balance. All oil palm growing regions showed a net gain with the exception of the western zone, where emissions due to land use change were judged to be substantial. Of the 11 alternative scenarios tested, only three resulted in Ceq. balances lower than the default and only two gave a negative balance.